Accessing the behavior and awareness of veterinary professionals towards antimicrobials use and antimicrobial resistance in Indian district - Dhayal, Virendra S.; Rehman, Bilal Ur; Krishnan, Ayana; Singh, Vijay Pal (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) poses a significant public health threat, and understanding the awareness and practices of healthcare professionals is crucial for its mitigation. Since the animal sector plays a key role in India's economy, we decided to explore the understanding of Antimicrobial Use (AMU) and AMR among veterinary professionals. The study aimed to evaluate the awareness and behavior of veterinarians and para-veterinarians working in the Jhunjhunu district, Rajasthan, India, concerning AMU and AMR. Questionnaire surveys were administered to them with closed-ended questions. The data was collected and subjected to statistical analysis to derive meaningful insights. The key findings highlight notable differences in certain behavioral aspects of antibiotic prescription among the two groups. It appears that 53.8% of veterinarians as compared to 25.8% para-veterinarians do not surely inform farmers about the importance of adhering to antibiotic withdrawal periods, thereby failing to raise awareness about proper antibiotic use. Moreover, para-veterinarians (46.6%) tend to engage less in evidence-based antibiotic prescription than veterinarians (81%). Furthermore, both groups exhibit a lower frequency of advice on Antimicrobial Susceptibility Testing (ABST), essential for informed prescribing decisions. Most significantly, both groups show a tendency to prefer critically important antibiotics for prescription, raising concerns about the escalating threat of AMR. This study thus emphasizes the areas that need targeted interventions to enhance responsible antimicrobial usage and curb the growth of AMR in the region.